Automatically engaging and disengaging gear box assembly - FRITZINGER; DANIEL D; HALL; CRAIG R (1997)
A gear box assembly for automatically engaging and disengaging an output gear which is non-rotatably concentrically mounted on a driven axle shaft attached to plural wheels in a children's ride-on toy is described. The assembly includes an electric motor with a pinion driving plural driven gears, and a yoke which is pivotable between two positions and provides a mount for at least one of the plural driven gears. In one position, the yoke pivotally engages the output gear and drives the vehicle's wheels, and in another position, the yoke pivotally disengages the output gear thereby allowing the vehicle's wheels to freely rotate without driving or back-driving the motor or other gears. In the preferred embodiment, the yoke is counterbalanced for rotation about a defined axis. In alternative embodiments, the yoke includes a friction member for developing friction between one of the driven gears to rotate the yoke into engagement.